Voltage-Gated Channel Mechanosensitivity: Fact or Friction? - Morris, Catherine E. (Frontiers in Physiology, 2011)
The heart is a continually active pulsatile fluid pump that generates forces by precisely timed and spaced engagement of contractile nano-machinery. This pump largely generates its own control signals, the most crucial of which involve precisely timed and spaced transmembrane ion fluxes. The timely opening and closing of the diverse voltage-gated channel (VGC) sub-types is indispensible for pulsatile pumping with the appropriate rhythm. VGCs are large membrane proteins with four voltagesensors around a central ion-selective pore that opens and closes under the influence of membrane voltage (Fig 1). The operation of VGCs is tuned, in a secondary fashion, by the mechanical state of the bilayers in which they are embedded{18},{36},{44}. I focus here on the possibility that in the highly mechanically active environment of the myocardium and its vasculature, VGCs feel and respond to changing bilayer structures. Do they collectively transduce mechanical signals and tune rhythmicity? I suggest that tools now available could help answer this question. Some might wish to first peruse a section at the end of this essay summarizing a few fundamentals about VGC kinetics and about the modulation of their kinetics by mechanical factors; see “Basic operation of a VGC...”. That section is preceded by a list of abbreviations used in the essay and by lists of situations that might be expected to reversibly or irreversibly alter VGC-bearing membranes in the heart.